Pengembangan Sistem Informasi Mahasiswa Universitas Amikom Purwokerto dengan Menggunakan Metode TOGAF - Anung Supriyadi; Arindia Nur Zahra; Epa Latifah; Ito Setiawan (Asosiasi Profesi Telekomunikasi Dan Informatika Indonesia, 2025)
Currently, the Amikom University Purwokerto student portal is still not equipped with a student data search feature that can make it easier to access related information. The unavailability of this feature can provide significant obstacles to various students' daily activities, especially in activities such as academic research, collaborative group work across study programs, and interactions between departments. The aim of this research is to apply the TOGAF framework which is expected to be able to help identify the root of the problem and provide a more comprehensive, systematic and effective solution in an effort to improve the functionality of this portal, so that it can better support students' academic needs. This research uses the TOGAF method which includes Understanding Business Context, Vision Architecture, Definition Architecture, and Transition Architecture. The result of this research is a flowchart design for the student data search feature which was created and analyzed using the Bizagi Modeler application which was compared between the design and the current process. Based on the results, it shows that the design of the student data search flow through Student Amikom Purwokerto is much faster and more efficient because the data search time is reduced from 40 minutes to 3 minutes.